The Lived Experiences and Perceptions of Public-School Employee in the Philippines: A PWD’s Perspective - Avila, Philip Gail; Osea, Eleanor; Gata, Ramona; Portea, Jackielene; De Leon, Natividad; Avila, Elda (IJBLE Scientific Publications Community Inc., 2023)
This study aimed to explore and describe the lived experiences of PWD employees in different designations; wherein, Administrative or School Head, Teacher, and Non-teaching or office personnel are the participants of the study. It was conducted at Northeastern part of the Philippines, specifically at region 4A and region V in the Philippines. The paper is qualitative type of research that utilized the van Kaam method of analysis as modified by Moustakas. The study verified the challenges encountered by PWD employees in their workplaces, the experiences and challenges were further categorized into